1991
DOI: 10.1097/00003446-199108000-00001
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Threshold Estimation using the “Chained-Stimuli” Technique for Auditory Brain Stem Response Measurement

Abstract: The "chained-stimuli" technique for rapid auditory brain stem response (ABR) threshold estimation involves lengthening the averaging time window and presenting a series ('khain") of click stimuli. Each stimulus chain contains, in addition to a silent interval, click stimuli of 10,20, 30, 40, 50, 60, and 70 dB nHL that are separated by 10 msec intervals. Using this method, the single averaged response to the chained-stimulus contains up to seven individual ABRs. The responses elicited by each level of click sti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

1996
1996
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 1 publication
1
7
0
Order By: Relevance
“…Our study used slightly adapted (but more clinically applicable) rates for the nonchained stimuli, and so our findings are more in line with studies that used higher presentation rates (e.g., Hamill, Hussung, & Sammeth, 1991).…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Our study used slightly adapted (but more clinically applicable) rates for the nonchained stimuli, and so our findings are more in line with studies that used higher presentation rates (e.g., Hamill, Hussung, & Sammeth, 1991).…”
Section: Discussionsupporting
confidence: 85%
“…There is scope to combine aspects of other chained-stimuli, perhaps adaptively including various intensity components in a manner similar to increasing-intensity click sequences (Hamill et al, 1991;Hamill et al, 1992).…”
Section: Discussionmentioning
confidence: 99%
“…Studies using multiple-intensity clicks and tone bursts have demonstrated time savings in the acquisition of cochlear and brainstem responses [Spoor, 1974;Hamill et al, 1991Hamill et al, , 1992Hoke et al, 1991]. Although adaptation appeared to have been minimal, some questions remain because the direct comparison of responses obtained from single and multiple stimulus presentations has only been reported for clicks [Hamill et al, 1992] and tone bursts separated by 1 octave [Mitchell et al, 1996].…”
Section: Discussionmentioning
confidence: 99%
“…The clinical application of auditory brainstem response (ABR) is often limited by the practical length of a test session [Mitchell and Clemis, 1977;Jerger et al, 1985;Burkard et al, 1990a;Hamill et al, 1991;Mitchell et al, 1996]. Conventional test sessions (without sedation or anesthesia) have a limit of about 1 h. This greatly limits the number of averaged responses that can be obtained and the range of frequencies and intensities that may be examined.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation